2019
DOI: 10.3892/ol.2019.10963
|View full text |Cite
|
Sign up to set email alerts
|

Impact of antiretroviral drugs on PD‑L1 expression and copy number gains with clinical outcomes in HIV‑positive and ‑negative locally advanced cervical cancers

Abstract: Cervical cancer has become a leading cause of death in both HIV-infected and uninfected women. Previous studies have revealed that antiretroviral therapy (ART) possesses anti-human papillomavirus (HPV) and antitumour properties, potentially serving as an anticancer agent and improving functional immunity in HIV-positive individuals. However, to the best of our knowledge, no studies have examined the association between ART and the clinical outcome of patients with pre-existing invasive cervical cancer. The cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Our previous study showed that tumors of HIV-infected cervical cancer patients who had undergone antiretroviral therapy (ART) had lower prevalence of PD-L1 immunopositivity, PD-L1 amplification, and polysomy compared with patients who did not receive ART and those that were HIV-negative. 14 Having additional expression data on PD-L1 and its encoding gene in HIV-positive patients would be useful for clinical management.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that tumors of HIV-infected cervical cancer patients who had undergone antiretroviral therapy (ART) had lower prevalence of PD-L1 immunopositivity, PD-L1 amplification, and polysomy compared with patients who did not receive ART and those that were HIV-negative. 14 Having additional expression data on PD-L1 and its encoding gene in HIV-positive patients would be useful for clinical management.…”
Section: Introductionmentioning
confidence: 99%
“…Only two of 19 (10.5%) had a PD‐L1–positive tumor, and response did not correlate with tumor PD‐L1 expression. ART exposure has been associated with decreased PD‐L1 expression in cervical cancer 23,24 . However, other groups have found that colorectal cancer and lung cancer in PLWH have similar PD‐L1 expression and PD‐1 expression of tumor‐infiltrating lymphocytes 25,26 …”
Section: Discussionmentioning
confidence: 98%
“…One of those two subjects had two sure has been associated with decreased PD-L1 expression in cervical cancer. 23,24 However, other groups have found that colorectal cancer and lung cancer in PLWH have similar PD-L1 expression and PD-1 expression of tumor-infiltrating lymphocytes. 25,26 Another objective of this study was to evaluate the effect of nivolumab on CD4/C8 populations and HIV viral load.…”
Section: Cd4 and Hiv Monitoringmentioning
confidence: 98%
“…Nelfinavir also interferes with late steps of adenovirus and herpesvirus replication in vitro , but it does not affect adenoviral cysteine protease or herpes serine protease ( Georgi et al, 2020 ; Kalu et al, 2014 ). Similarly, lopinavir could act against papillomaviruses through its interactions with host targets ( Barillari et al, 2018 ; Batman et al, 2011 ; Loharamtaweethong et al, 2019 ; Zehbe et al, 2011 ).…”
Section: Hiv and Anti-hiv Therapymentioning
confidence: 99%